At great risk : memoirs of rescue during the Holocaust - Lang, Eva 1930- (The Azrieli series of Holocaust survivor memoirs, 2021)
"Fishel Goldig was born in 1933, in Mielnica (now Melnytsia-Podilska), Ukraine, and lives in Montreal, Quebec, where he is a Holocaust educator and theatre performer. David Korn was born in Brno, Czechoslovakia, in 1937 and lives in Halifax, Nova Scotia. Eva Lang was born in Brussels, Belgium, in 1930 and lives in Netanya, Israel. Josef Meshorer was born in Warsaw, Poland, in 1932 and passed away in Toronto, Ontario, in 2013."